NEW APPROACH FOR MANNHEIM CURVES IN TERMS OF INEXTENSIBLE FLOWS IN E-3 - Körpınar, Talat; Ergut, Mahmut (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2017)
In this work, we study the properties of the Mannheim curves in terms of inextensible flows in E-3. Using the Frenet frame of the given curve, we present partial differential equations. We give some characterizations for curvatures of a curve in E-3.
Keywords: Mannheim curve; Fluid flow; Frenet frame; Partial differential equation